2′-Hydroxy-4-methylsulfonylchalcone enhances TRAIL-induced apoptosis in prostate cancer cells. Issue 1 (January 2015) - Ismail, Bassel; Fagnere, Catherine; Limami, Youness; Ghezali, Lamia; Pouget, Christelle; Fidanzi, Chloë; Ouk, Catherine; Gueye, Rokhaya; Beneytout, Jean-Louis; Duroux, Jean-Luc; Diab-Assaf, Mona; Leger, David Y.; et al.
<x xml:space="preserve">Abstract</x> Prostate cancer is the most common malignant cancer in men and the second leading cause of cancer deaths. Previously, we have shown that 2′-hydroxy-4-methylsulfonylchalcone (RG003) induced apoptosis in prostate cancer cell lines PC-3 and DU145. Although tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising anticancer agent, some cancer cells are resistant to TRAIL treatment. PC-3 and LNCaP prostatic cancer cell lines have been reported to be resistant to TRAIL-induced apoptosis. Here, we show for the first time that RG003 overcomes TRAIL resistance in prostate cancer cells. RG003 can enhance TRAIL-induced apoptosis through DR5 upregulation and downregulation of Bcl-2, PI3K/Akt, NF-κB, and cyclooxygenase-2 (COX-2) survival pathways. When used in combined treatment, RG003 and TRAIL amplified TRAIL-induced activation of apoptosis effectors and particularly activation of caspase-8 and the executioner caspase-3, leading to increased poly-ADP-ribose polymerase cleavage and DNA fragmentation in prostate cancer cells. Furthermore, we showed that RG003 reduced COX-2 expression in cells. Previously, we showed that COX-2 was involved in resistance to an apoptosis mechanism; then, its inhibition by RG003 could render cells more sensitive to TRAIL treatment. We showed that nuclear factor-κB activation was inhibited after RG003 treatment. This inhibition was correlated with reduction in COX-2 expression and induction of apoptosis. Overall, we conclude, for the first time, that RG003 can enhance TRAIL-induced apoptosis in human prostate cancer cells. The significance of our in-vitro study with RG003 and TRAIL combined is very encouraging, suggesting the relevance of testing this combined treatment in xenograft animal models.